Lay-off restraints, employment subsidies, and the demand for labour - Horst Siebert; Ngo Van Long (Universität Konstanz, Fakultät für Wirtschaftswissenschaften und Statistik, 1984)
The paper introduces the concept of a firm's normal employment level as a weighted average of past employment levels and it analyzes the impact of an incentive scheme in which a firm receives a reward (or pays a penalty) when it deviates above (below) its normal employment level. The result is that such an institutional setting may imply a cyclical demand in labour. Thus, institutional arrangements may .be responsible for business cycles.
Keywords: 330